2018
DOI: 10.1016/j.jaut.2018.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous IL-10 maintains immune tolerance but IL-10 gene transfer exacerbates autoimmune cholangitis

Abstract: The immunomodulatory effect of IL-10 as an immunosuppressive and anti-inflammatory cytokine is well known. Taking advantage of our established mouse model of autoimmune cholangitis using 2-octynoic acid conjugated ovalbumin (2-OA-OVA) induction, we compared liver pathology, immune cell populations and antimitochondrial antibodies between IL-10 knockout and wild type mice immunized with 2-OA-OVA. At 10 weeks post immunization, portal inflammation and fibrosis were more severe in 2-OA-OVA immunized IL-10 knockou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…DCs interact with a variety of immune cells to regulate the activities of other immune cells [ 25 ]. The reduction of the IL-10 expression suggests a dysfunctional state of immune regulatory cells [ 23 , 26 ]. A novel point of the present study is that we found an overexpression of Tert in DCs of subjects with AR, which could disrupt the tolerogenic feature of TolDCs.…”
Section: Discussionmentioning
confidence: 99%
“…DCs interact with a variety of immune cells to regulate the activities of other immune cells [ 25 ]. The reduction of the IL-10 expression suggests a dysfunctional state of immune regulatory cells [ 23 , 26 ]. A novel point of the present study is that we found an overexpression of Tert in DCs of subjects with AR, which could disrupt the tolerogenic feature of TolDCs.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α is an important mediator of immune protection, promoting cell proliferation and differentiation and enhancing the killing ability of killer cells such as T cells. IL-10 is generally considered as a protective cytokine that promotes immune regulation, and IL-17 is involved in host defense against fungi, extracellular bacteria, and other eukaryotes [39,40]. Previous studies have shown that the effects of polysaccharides on improving immune function are closely associated to their ability to promote cytokine secretion [3,[41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…We agree with Dr Hydes and Prof. Khakoo on the relevance of NK cells in bridging innate with adaptive immunity in PBC, with one characteristic being enhanced interferon (IFN)-c, other than IL-10, production. 4,5 In particular, NK cell cytotoxicity against biliary epithelial cells (BECs) is initiated only after toll-like receptor (TLR) 3-mediated NK stimulation and TLR4-mediated monocyte stimulation. This function is regulated by a large family of inhibitory NK cell receptors, including killer-cell immunoglobulin-like receptors and C-lectin type molecules, which recognize major histocompatibility complex (MHC) class I present on autologous cells.…”
Section: To the Editormentioning
confidence: 99%